Stowarzyszenie Inwestorów Indywidualnych na mapie interesów uczestników rynku kapitałowego w Polsce - Rzepka, Artur (Polish individual investors' association on the map of interests on the Polish capital market, 2005)
Capital market is under the consistent impact of several groups of interest. Their interests are often in conflict, but also can be common. Groups of capital market actors have to establish a representation in order to secure their interests on capital market. Polish Individual Investors’ Association was founded in 1999. The association tries to realize its objectives by multiple activities, aimed to investors and other stakeholders. It has several achievements, among them the most important are: number of above 1500 members, 18 local councils, yearly conference named WallStreet, quarterly magazine “Akcjonariusz” etc. The association also encounters some problems, such as: unsteady financial sources and lack of club goods which could be positive selective incentives for members. Polish Individual Investors’ Association will have the chance to achieve success and balance interests of others capital market members if it develops better financial sources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1090, s. 174-185